(untitled) (MCIT: Proceedings of International scientific and practical conference, 2025)
У статті розглянуто доцільність використання теплоти відхідних димових газів в контактному теплоутилізаторі. Представлено результати експериментального дослідження процесу нагріву води залежно від густини зрошення робочої ділянки, швидкості та температури газів, висоти робочого каналу. Отримано значення граничної температури нагріву води для умов барботажного режиму течії. запропоновано співвідношення для визначення граничної густини зрошення та максимального теплового навантаження контактного утилізатора теплоти. The article examines the feasibility of using the heat of exhaust flue gases in contact heat utilizer. The results of an experimental study of the process of heating water depending on the density of irrigation of the working area, the speed and temperature of gases, the height of the working channel are presented. The value of maximum temperature of water heating is obtained in the conditions of the bubbling flow mode. Correlation for determinftion of maximum irrigation density and the maximum heat load of the contact heat utilizer.